Methodology of film criticism: the journal Movie and the great tradition (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
During the sixties, the journal Movie inherits from Cahiers du cinéma the preferencies for a politique des auteurs and for certain american films. However, never abandoning this tendency towards a “cinema of directors”, the british journal develops a rigorous method of formal analysis and detailed close readings. Some of its members try to apply to cinema the concepts elaborated by F. R. Leavis and the journal Scrutiny in reference to literary criticism. It is precisely this analytic method that will be questioned during the boom of structuralism and post structuralism to which the journal Screen will be asociated in the 70s.
Keywords: Movie; F. R. Leavis; close reading; Screen